Pregunta
upstudy study bank question image url

answers: 1.. \( x+y=10 \) \[ x-y=2 \] 2. \( x+y=5 \) 3. \( 2 x+3 y=11 \) \( 4 y-2 x=10 \) 4. \[ 3 x+2 y=13 \] \[ 2 x+3 y=18 \] \[ 8 x=7-3 y \] 6. 5. \( 8 x=7-3 y \) \( 3 x+4 y=3 \) \[ 9 y=-20 x+13 \] \( 6 x=7-10 y \) 7. \( 2 y=3 x+3 \) 8. \( 3 y-4 x=4 \) \( 2 y=x \) \( 8 x-1=-2 y \) 9. \( 4 y=-x \) 10. \[ \begin{array}{l} 3 y+6=6 x \\ x=2 y-2 \end{array} \]

Ask by King Medina. in South Africa
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the solutions to the systems of equations: 1. \( x = 6 \), \( y = 4 \) 2. Infinite solutions: \( y = 5 - x \) 3. \( x = 1 \), \( y = 3 \) 4. No solution 5. No solution 6. Infinite solutions: \( y = \frac{3}{2}x + \frac{3}{2} \) 7. No solution 8. Infinite solutions: \( y = -\frac{1}{4}x \) 9. \( x = 2 \), \( y = 2 \)

Solución

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3y+6=6x\\x=2y-2\end{array}\right.\) - step1: Substitute the value of \(x:\) \(3y+6=6\left(2y-2\right)\) - step2: Expand the expression: \(3y+6=12y-12\) - step3: Move the expression to the left side: \(3y-12y=-12-6\) - step4: Add and subtract: \(-9y=-12-6\) - step5: Add and subtract: \(-9y=-18\) - step6: Change the signs: \(9y=18\) - step7: Divide both sides: \(\frac{9y}{9}=\frac{18}{9}\) - step8: Divide the numbers: \(y=2\) - step9: Substitute the value of \(y:\) \(x=2\times 2-2\) - step10: Calculate: \(x=2\) - step11: Calculate: \(\left\{ \begin{array}{l}x=2\\y=2\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=2\\y=2\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(2,2\right)\) Solve the system of equations \( x+y=10;x-y=2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+y=10\\x-y=2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=10-y\\x-y=2\end{array}\right.\) - step2: Substitute the value of \(x:\) \(10-y-y=2\) - step3: Subtract the terms: \(10-2y=2\) - step4: Move the constant to the right side: \(-2y=2-10\) - step5: Subtract the numbers: \(-2y=-8\) - step6: Change the signs: \(2y=8\) - step7: Divide both sides: \(\frac{2y}{2}=\frac{8}{2}\) - step8: Divide the numbers: \(y=4\) - step9: Substitute the value of \(y:\) \(x=10-4\) - step10: Calculate: \(x=6\) - step11: Calculate: \(\left\{ \begin{array}{l}x=6\\y=4\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=6\\y=4\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(6,4\right)\) Solve the system of equations \( 2 x+3 y=11;4 y-2 x=10 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x+3y=11\\4y-2x=10\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{11-3y}{2}\\4y-2x=10\end{array}\right.\) - step2: Substitute the value of \(x:\) \(4y-2\times \frac{11-3y}{2}=10\) - step3: Simplify: \(7y-11=10\) - step4: Move the constant to the right side: \(7y=10+11\) - step5: Add the numbers: \(7y=21\) - step6: Divide both sides: \(\frac{7y}{7}=\frac{21}{7}\) - step7: Divide the numbers: \(y=3\) - step8: Substitute the value of \(y:\) \(x=\frac{11-3\times 3}{2}\) - step9: Calculate: \(x=1\) - step10: Calculate: \(\left\{ \begin{array}{l}x=1\\y=3\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=1\\y=3\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(1,3\right)\) Solve the system of equations \( 3 x+2 y=13;2 x+3 y=18;8 x=7-3 y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x+2y=13\\2x+3y=18\\8x=7-3y\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{13-2y}{3}\\2x+3y=18\\8x=7-3y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}2\times \frac{13-2y}{3}+3y=18\\8\times \frac{13-2y}{3}=7-3y\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}\frac{2\left(13-2y\right)}{3}+3y=18\\\frac{8\left(13-2y\right)}{3}=7-3y\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}y=\frac{28}{5}\\\frac{8\left(13-2y\right)}{3}=7-3y\end{array}\right.\) - step5: Substitute the value of \(y:\) \(\frac{8\left(13-2\times \frac{28}{5}\right)}{3}=7-3\times \frac{28}{5}\) - step6: Simplify: \(\frac{24}{5}=-\frac{49}{5}\) - step7: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step8: Rewrite: \((x, y) \in \varnothing\) Solve the system of equations \( 3 y-4 x=4;2 y=x;8 x-1=-2 y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3y-4x=4\\2y=x\\8x-1=-2y\end{array}\right.\) - step1: Rewrite the expression: \(\left\{ \begin{array}{l}3y-4x=4\\x=2y\\8x-1=-2y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}3y-4\times 2y=4\\8\times 2y-1=-2y\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}-5y=4\\16y-1=-2y\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}y=-\frac{4}{5}\\16y-1=-2y\end{array}\right.\) - step5: Substitute the value of \(y:\) \(16\left(-\frac{4}{5}\right)-1=-2\left(-\frac{4}{5}\right)\) - step6: Simplify: \(-\frac{69}{5}=\frac{8}{5}\) - step7: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step8: Rewrite: \((x, y) \in \varnothing\) Solve the system of equations \( 8 x=7-3 y;3 x+4 y=3;9 y=-20 x+13;6 x=7-10 y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}8x=7-3y\\3x+4y=3\\9y=-20x+13\\6x=7-10y\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{7-3y}{8}\\3x+4y=3\\9y=-20x+13\\6x=7-10y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}3\times \frac{7-3y}{8}+4y=3\\9y=-20\times \frac{7-3y}{8}+13\\6\times \frac{7-3y}{8}=7-10y\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}\frac{3\left(7-3y\right)}{8}+4y=3\\9y=-\frac{5\left(7-3y\right)}{2}+13\\\frac{3\left(7-3y\right)}{4}=7-10y\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}y=\frac{3}{23}\\9y=-\frac{5\left(7-3y\right)}{2}+13\\\frac{3\left(7-3y\right)}{4}=7-10y\end{array}\right.\) - step5: Substitute the value of \(y:\) \(\left\{ \begin{array}{l}9\times \frac{3}{23}=-\frac{5\left(7-3\times \frac{3}{23}\right)}{2}+13\\\frac{3\left(7-3\times \frac{3}{23}\right)}{4}=7-10\times \frac{3}{23}\end{array}\right.\) - step6: Simplify: \(\left\{ \begin{array}{l}\frac{27}{23}=-\frac{81}{23}\\\frac{114}{23}=\frac{131}{23}\end{array}\right.\) - step7: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step8: Rewrite: \((x, y) \in \varnothing\) Let's solve the systems of equations step by step based on the provided inputs. ### 1. System: \[ x + y = 10 \] \[ x - y = 2 \] **Solution:** By solving these equations, we find: \[ (x, y) = (6, 4) \] ### 2. System: \[ x + y = 5 \] **Solution:** This is a single equation with infinite solutions. We can express \(y\) in terms of \(x\): \[ y = 5 - x \] ### 3. System: \[ 2x + 3y = 11 \] \[ 4y - 2x = 10 \] **Solution:** By solving these equations, we find: \[ (x, y) = (1, 3) \] ### 4. System: \[ 3x + 2y = 13 \] \[ 2x + 3y = 18 \] \[ 8x = 7 - 3y \] **Solution:** This system has no solution, which can be expressed as: \[ (x, y) \in \varnothing \quad \text{(No solution)} \] ### 5. System: \[ 8x = 7 - 3y \] \[ 3x + 4y = 3 \] \[ 9y = -20x + 13 \] \[ 6x = 7 - 10y \] **Solution:** This system also has no solution: \[ (x, y) \in \varnothing \quad \text{(No solution)} \] ### 6. System: \[ 2y = 3x + 3 \] **Solution:** This is a single equation with infinite solutions. We can express \(y\) in terms of \(x\): \[ y = \frac{3}{2}x + \frac{3}{2} \] ### 7. System: \[ 3y - 4x = 4 \] \[ 2y = x \] \[ 8x - 1 = -2y \] **Solution:** This system has no solution: \[ (x, y) \in \varnothing \quad \text{(No solution)} \] ### 8. System: \[ 4y = -x \] **Solution:** This is a single equation with infinite solutions. We can express \(y\) in terms of \(x\): \[ y = -\frac{1}{4}x \] ### 9. System: \[ 3y + 6 = 6x \] \[ x = 2y - 2 \] **Solution:** By solving these equations, we find: \[ (x, y) = (2, 2) \] ### Summary of Solutions: 1. \( (x, y) = (6, 4) \) 2. Infinite solutions: \( y = 5 - x \) 3. \( (x, y) = (1, 3) \) 4. No solution 5. No solution 6. Infinite solutions: \( y = \frac{3}{2}x + \frac{3}{2} \) 7. No solution 8. Infinite solutions: \( y = -\frac{1}{4}x \) 9. \( (x, y) = (2, 2) \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

Ever wondered why solving systems of equations is like playing a puzzle game? Each equation is a piece of the puzzle, and when you find the solution, you reveal the whole picture! Historically, systems of equations have their roots in the works of mathematicians like Euclid and Diophantus, who laid the groundwork for algebraic methods that later evolved into what we use in modern math. When applying these concepts in real life, think of a cash register balancing calculations or planning ingredients for a recipe. For example, if you know your total budget and the price of each item, you can set up equations to figure out quantities—just like blending flavors in a dish to achieve the perfect taste.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad